2016
DOI: 10.1111/jocn.13302
|View full text |Cite
|
Sign up to set email alerts
|

District nurses' perspectives on detecting mental health problems and promoting mental health among community‐dwelling seniors with multimorbidity

Abstract: Aims and objectivesTo describe district nurses' perspectives on detecting mental health problems and promoting mental health among homebound older people with multimorbidity.BackgroundMental health problems among older people with multiple chronic conditions, that is, multimorbidity, are challenging issues. These patients' homes often serve as arenas in which district nurses can promote health. Mental health promotion must be studied in greater depth within primary care because older people with multimorbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(58 citation statements)
references
References 25 publications
1
46
0
11
Order By: Relevance
“…However, yet older people with mental disorders' stated they preferred to consult with primary care staff rather than specialist in mental health (Lester et al, ). Lack of resources, such as guidelines or structured goals for mental health care in their settings, and lack of a structured forum for collaboration between health care providers and their patients with mental health problems were also barriers for district nurses working at the community level (Grundberg, Hansson, Hillerås, & Religa, ). One study suggested that nurses needed to develop interview techniques for assessing older people with mental health problems (Grundberg et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, yet older people with mental disorders' stated they preferred to consult with primary care staff rather than specialist in mental health (Lester et al, ). Lack of resources, such as guidelines or structured goals for mental health care in their settings, and lack of a structured forum for collaboration between health care providers and their patients with mental health problems were also barriers for district nurses working at the community level (Grundberg, Hansson, Hillerås, & Religa, ). One study suggested that nurses needed to develop interview techniques for assessing older people with mental health problems (Grundberg et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The review also represents the perspectives of participants, contributing to understanding the issues relating to active ageing, the service needs gaps for older people with mental health problems in rural areas, and the facilitators and barriers for working with older people in communities (Grundberg et al, 2016;Wilhelmsson & Lindberg, 2009). Participants were primary care providers including district nurses, and multidisciplinary teams in the community health services, older people living in the community, and older people with mental disorders (Goodman et al, 2011;Grundberg et al, 2014;Kim, 2009;Murray et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dos 10 artigos selecionados [9][10][11][12][13][14][15][16][17][18] , todos publicados no período de 2014 a 2018, um é do Canadá 11 , três de países europeus (Suécia, Portugal, Espanha) 12,14,17 e seis do Brasil 9,10,13,15,16,18 . Em 2014 foram publicados dois 9,14 , em 2015 três 13,15,17 , em 2016 quatro 11,12,16,18 e apenas um em 2018 10…”
Section: Resultsunclassified
“…[9,11] As a result, older people with mental illness presenting to primary care settings are often not diagnosed and often go untreated. [1,[12][13][14][15] The aim of this study was to develop and test preliminary results of a new survey instrument: the "Promoting Active Ageing in Older People with Mental Disorders Scale" (PAA-MD).…”
Section: Introductionmentioning
confidence: 99%